2020
DOI: 10.1002/pa.2357
|View full text |Cite
|
Sign up to set email alerts
|

Why did I buy this? Purchase regret and repeat purchase intentions: A model and empirical application

Abstract: This study investigates consumer repurchase behavior and purchases regret in the context of a Steadily Increasing Discount (SID) strategy. A quantitative research approach based on a full‐scaled administrative survey is adopted in the framework of the regret theory. Mall intercept technique is used to collect the cross‐sectional data from respondents. To establish the proposed relational paths, structural equation modeling is applied. The findings of the study suggest that confirmation, price consciousness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…The AVE values and CR values for all constructs and the discriminant validity index summary are reported in Table 2. 2, the study found all AVE and CR exceed their threshold values of 0.5 and 0.6 respectively (Kashif et al, 2015, Noor et al, 2015, Yusof et al, 2017Aziz et al, 2016;Mohamad et al, 2016Mohamad et al, , 2017Mohamad et al, , 2018Mohamad et al, , 2019Sarwar et al, 2020). Thus, the study can conclude that the Convergent Validity and Composite Reliability for all latent constructs in the model have been achieved.…”
Section: Results and Discussion Confirmatory Factor Analysis (Cfa)mentioning
confidence: 88%
See 2 more Smart Citations
“…The AVE values and CR values for all constructs and the discriminant validity index summary are reported in Table 2. 2, the study found all AVE and CR exceed their threshold values of 0.5 and 0.6 respectively (Kashif et al, 2015, Noor et al, 2015, Yusof et al, 2017Aziz et al, 2016;Mohamad et al, 2016Mohamad et al, , 2017Mohamad et al, , 2018Mohamad et al, , 2019Sarwar et al, 2020). Thus, the study can conclude that the Convergent Validity and Composite Reliability for all latent constructs in the model have been achieved.…”
Section: Results and Discussion Confirmatory Factor Analysis (Cfa)mentioning
confidence: 88%
“…The Confirmatory Factor Analysis outputs are presented in Figure 2. The measurement model in Figure 2 showed the required Fitness Indexes satisfactorily (RMSEA = 0.075, CFI = 0.957, ChiSq/df = 2.841), so the construct validity was achieved (Mohamad et al, 2018(Mohamad et al, , 2019Awang 2019, 2020;Bahkia et al, 2019, Sarwar et al, 2020, Afthanorhan et al, 2020. (Asnawi et al, 2019;Rahlin et al, 2019b;Majid et al, 2019).…”
Section: Results and Discussion Confirmatory Factor Analysis (Cfa)mentioning
confidence: 94%
See 1 more Smart Citation
“…Harris et al (2016) have shown that cleanliness is the ultimate major shopping attribute for both regular and casual retail customers in general. Sarwar et al (2020) said the clean shops would create images of cleanliness, satisfaction or extravagance. The appearance of the store (such as a shop is fine, confident, pleasant etc.)…”
Section: Cleanliness and Intention To Purchasementioning
confidence: 99%
“…(2018) and Sarwar et al. (2020) have also examined the relationship between post‐purchase cognitive dissonance (or regret) and price consciousness. However, cognitive differences that may affect these variables in common are yet unexplored.…”
Section: Introductionmentioning
confidence: 99%